Associations among Mammary Ultrasound Measurements, Milk Yield of Non-Dairy Ewe Lambs and the Growth of Their Single Lambs - Haslin E; Corner-Thomas RA; Kenyon PR; Peterson SW; Morris ST; Blair HT (MDPI (Basel, Switzerland), 2021)
Mammary cistern size was positively correlated with milk yield of mature dairy ewes, but the association in ewe lambs is unknown. This experiment aimed to examine the associations between mammary ultrasound measurements and the milk yield of ewe lambs at one year of age and to determine the accuracy of using maternal mammary ultrasound to predict single lamb growth rates. Single-bearing ewe lambs (n = 45) were randomly selected and 30 were milked once at weeks three (W3), five (W5), and seven (W7) of lactation. Mammary ultrasound scans were performed at day 110 of pregnancy, W3, W5, W7, and weaning (L69). Single lambs (n = 30) were weighed at birth and at each mammary scanning event. Udder measurements explained 26.8%, 21.4%, and 38.4% of the variation in milk yield at W3, W5 and W7, respectively, and 63.5% and 36.4% of the variation in single lamb growth to W3 and to L69. This ultrasound technique was more accurate in predicting single lamb growth to W3 than milk yield and may enable the identification of pregnant ewe lambs whose progeny would have greater growth rates. More research is needed to identify accurate indicators of superior milk yield and determine whether ultrasound could be used to select ewe lambs.
Keywords: fat pad; gland cistern; parenchyma; udder morphology; ultrasonography